2021
DOI: 10.3390/ijms22169031
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Neuronal Nicotinic Receptors Inhibits Acetylcholine Release in the Neuromuscular Junction by Increasing Ca2+ Flux through Cav1 Channels

Abstract: Cholinergic neurotransmission is a key signal pathway in the peripheral nervous system and in several branches of the central nervous system. Despite the fact that it has been studied extensively for a long period of time, some aspects of its regulation still have not yet been established. One is the relationship between the nicotine-induced autoregulation of acetylcholine (ACh) release with changes in the concentration of presynaptic calcium levels. The mouse neuromuscular junction of m. Levator Auris Longus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Neuromuscular synapses of vertebrates contain presynaptic AchRs, which implement a modulatory action of ACh on its own release. Despite a long history of studies showing the effects of both AChR activators and blockers on quantal ACh secretion [ 23 , 24 , 25 , 26 , 27 , 28 ], there is still no consensus on the role of presynaptic ionotropic nicotinic (nAChR) and metabotropic muscarinic (mAChRs) receptors at the motor-nerve terminals in modulation of the kinetics of evoked ACh release. The data about the effects of nAChR blocker d-tubocurarine [ 29 ] and muscarinic agonists on the synaptic delays in the neuromuscular junctions [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ] suggest the participation of AChRs in regulation of the time course of ACh release.…”
Section: Presynaptic Acetylcholine Receptors Modulate the Kinetics Of...mentioning
confidence: 99%
See 2 more Smart Citations
“…Neuromuscular synapses of vertebrates contain presynaptic AchRs, which implement a modulatory action of ACh on its own release. Despite a long history of studies showing the effects of both AChR activators and blockers on quantal ACh secretion [ 23 , 24 , 25 , 26 , 27 , 28 ], there is still no consensus on the role of presynaptic ionotropic nicotinic (nAChR) and metabotropic muscarinic (mAChRs) receptors at the motor-nerve terminals in modulation of the kinetics of evoked ACh release. The data about the effects of nAChR blocker d-tubocurarine [ 29 ] and muscarinic agonists on the synaptic delays in the neuromuscular junctions [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ] suggest the participation of AChRs in regulation of the time course of ACh release.…”
Section: Presynaptic Acetylcholine Receptors Modulate the Kinetics Of...mentioning
confidence: 99%
“…There are a large amount of data about the effects of nAChRs agonists and antagonists on the ACh quanta number released in response to nerve stimulus [ 23 , 25 , 26 ]. Nevertheless, the results of the investigations about changes in the kinetics of ACh quanta release under specific nAChR modulation are scarce.…”
Section: Presynaptic Acetylcholine Receptors Modulate the Kinetics Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotinic acetylcholine receptors (nAChRs) are transmembrane ligand-gated ion channels, which are widely distributed in the central and peripheral nervous systems of primitive and evolutionary advanced organisms [ 1 , 2 ]. As a member of the ligand-gated ion channel family, nAChRs play a vital role in regulating signal transmission between nerve and muscle [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the work by Zhilyakov et al, the authors reported the results from their investigation on the relationship between the nicotine-induced autoregulation of acetylcholine (ACh) release and the changes in the concentration of presynaptic calcium levels [ 61 ]. For this purpose, they used a pharmacological approach, electrophysiological techniques, and a method for the optical registration of changes in calcium levels in the motor nerve endings.…”
mentioning
confidence: 99%